Impact of ICT on Teaching Practices in India - Anchal Sharma (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2021)
Integration of Information and Communication in the classroom has been transforming the way learners are learning today. Teachers in India are also experimenting with innovative ways to teach with the help of ICT tools. They are leveraging various digital platforms for planning their lessons, delivering them in the classroom setup or virtually, and conducting the assessment as well. Educational technology is offering effective ways to reach different types of learners and assess their understanding in more than one way. Teachers' well-equipped preparation with ICT tools and facilities is one of the main factors in the success of technology-based teaching and learning. The Indian government has been persistent in implementing policies to encourage technology-driven innovations in the education sector and encouraging educators to adopt and integrate ICT. Although the perception of Indian teachers towards the use of ICT is positive, still need more support with the infrastructure and training especially in the rural regions. This paper will cover how technology has impacted the teaching practices, perceptions of teachers about the use of technology in the classroom, and their professional development.
Keywords: 330